2018
DOI: 10.1177/2050312118757387
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors associated with change in pain and disability outcomes in chronic low back pain patients treated by physiotherapist: A systematic review

Abstract: Background:Almost 80% of people have low back pain at least once in their life. Clinical guidelines emphasize the use of conservative physiotherapy and the importance of staying active. While the psychological factors predicting poor recovery following surgical intervention are understood, the psychosocial factors associated with poor outcomes following physiotherapy have yet to be identified.Methods:Electronic searches of PubMed, Medline, CINAHL, PsycINFO and EBSCO were conducted using terms relating to psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 30 publications
3
68
0
4
Order By: Relevance
“…The reference lists of included studies and related systematic reviews [22,[31][32][33][34][35][36] will be searched. Citation searching of questionnaires for depressive symptoms that have been utilized in LBP populations will also be conducted: Center for Epidemiologic Studies Depression Scale, Beck Depression Index, Patient Health Questionnaire-9, and Depression Scale of the Hospital Anxiety and Depression Scale.…”
Section: Study Designs/characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference lists of included studies and related systematic reviews [22,[31][32][33][34][35][36] will be searched. Citation searching of questionnaires for depressive symptoms that have been utilized in LBP populations will also be conducted: Center for Epidemiologic Studies Depression Scale, Beck Depression Index, Patient Health Questionnaire-9, and Depression Scale of the Hospital Anxiety and Depression Scale.…”
Section: Study Designs/characteristicsmentioning
confidence: 99%
“…To our best knowledge, a systematic review examining the impact of depressive symptoms and depression on health care utilization in adults with LBP has not been previously conducted. Previous systematic reviews examining depressive symptoms and depression as prognostic factors affecting clinical or work-related outcomes for LBP require updating, as literature searches were completed before or up to early 2016 [22,[31][32][33][34][35][36]. Of these, the reviews with most recent literature searches were conducted by Alhowimel [22].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of low back pain (LBP) continues to rise, despite the increasing technological advancement in the medical field [1][2][3]. Following the natural course and history, episodes of LBP increase healthcare utilization and lead more patients into chronic stages [4,5]. A clear association was demonstrated between length of disability and healthcare cost, with 86% of episodes less than one month yielding only 11% of all costs [6].…”
Section: Introductionmentioning
confidence: 99%
“…A clear association was demonstrated between length of disability and healthcare cost, with 86% of episodes less than one month yielding only 11% of all costs [6]. This reveals the importance of preventing and reducing the frequency of patients who transition from acute to chronic stages [5,7]. A biomedical, pathoanatomical model negatively influence the patient's overall status and those dealing with chronic low back pain [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Research has reported that 20% of individuals with OA experience symptoms of depression and anxiety 196 , and that depression is associated with decreased physical activity participation 197,198 . Higher fear of movement, anxiety, depression, catastrophizing 199 and lower pain self-efficacy 200 are all associated with pain 201 , and related to disability 200,202 . Low levels of self-efficacy have been linked to higher disability in individuals with OA of the knee and hip 203 .…”
Section: Contextual Factors In Oamentioning
confidence: 99%